Comparison of Scoring Systems in Predicting Stone-Free Rate in Flourless Retrograde Intrarenal Surgery - Arianto, Eko; Astram, Ari; Toreh, Christof; Wihono, Frendy; Krishna, Mahesa (Universitas Sam Ratulangi, 2025)
Abstract: Thus far, there is no standardised method for predicting outcomes from fluoro-less retrograde intrarenal surgery (RIRS) procedure. This study aimed to compare scoring systems in predicting stone-free rate (SFR) in RIRS patients This was an observational and analytical study with a retrospective cohort design. Samples were obtained from medical records of Dr. J. H. Awaloei Hospital from March 2022 to October 2023. This study only analyzed three scoring systems: Guy's Stone Score (GSS), Resorlu-Unsal Stone Score (RUSS), and Seoul National University Renal Stone Complexity Score (S-ReSC). The results obtained 219 patients with an average age of 55 years, GSS grade I in 108 patients, and grade II in 50 patients. Related to RUSS score, 43 patients got a score of 1, 108 got a score of 2, and 60 got a score of 60. Meanwhile, S-ReSC score was at a high level with a percentage of 65.3%, 20.4% at the medium level, and 14.4% at the low level. Moreover, GSS sensitivity 76%, specificity 75%, PPV 93.2%, NPV 41.1%, AUC 75%; RUSS score sensitivity 75.4%, specificity 62.2%, PPV 90%, NPV 36.2%, AUC 70%; S-ReSC score sensitivity 71%, specificity 77.5%, PPV 93.4%, NPV 37.3%, AUC 72%. In conclusion, Guy's Stone Score, Resorlu-Unsal Stone Score, and Seoul National University Renal Stone Complexity Score have similar abilities in predicting stone-free rate. Further research is needed with a larger sample size or population to confirm the findings of this study. Keywords: nephrolithiasis; stone-free rate; scoring system; retrograde intrarenal surgery